Comparative isolation of serum ? plus pre ? lipoproteins of human and various domestic animal species by dextran sulfate/MnCl2 and sodium phosphotungstate/MgCl2 precipitation methods - Ileri, T; Guldur, T (Tubitak Scientific & Technological Research Council Turkey, 2002)
Lipoproteins are water soluble complexes through which various lipids are transported between the various tissues for storage and utilization Association of lipoproteins with risk of coronary heart disease and various types of dyslipoproteinemias necessitate the quantification of the individual lipoprotein classes The study was undertaken to compare the concentrations of precipitation reagents (dextran sulfate/MnCl2 sodium phosphotungstate/MgCl2) necessary in order to precipitate beta+pre beta lipoproteins in human and various animal sera To this end the serum beta+pre beta lipoproteins of human and various animal species were precipitated using various methods The lipoproteins precipitated were separated and identified by agarose gel electrophoresis Dextran sulfate/MnCl2 at the concentration used for human serum resulted in complete precipitation of beta+pre beta lipoprotein of sera from all animal species In the sodium phosphotungstate/MgCl2 precipitation method beta+pre beta lipoproteins of goat and sheep were precipitated by two times more sodium phosphotungstate/MgCl2 than that required for human serum beta+pre beta lipoproteins Also in other animal species beta+pre beta lipoproteins were precipitated by the same sodium phosphotungstate/MgCl2 concentration It was concluded that the concentrations of polyanion/divalent cation used for the precipitations of serum beta+pre beta lipoproteins differ between human and several animal species The existing differences might be attributed to the variations in charge densities of lipoproteins surfaces as well as to dissimilarities in lipid compositions of the lipoproteins between species.
Keywords: lipoprotein isolation; precipitation; polyanion; divalent cation; serum